Isolation, peroxisome proliferator-activated receptor-gamma transcription, glucose uptake, and molecular docking of tetramethoxyflavonoids from the leaves of Rourea mimosoides (Vahl) Planch. - Che Puteh Osman&, Norhafizoh Abdul Somat&, Zuriati Zahari, Syahrul Imran&, Mohd Ilham Adenan (Journal of Applied Pharmaceutical Science, 2021)
Rourea mimosoides (Vahl) Planch. is used traditionally to treat various diseases. The ethanolic leaves extract was found to increase the transcription of peroxisome proliferator-activated receptor-gamma (PPARγ). Therefore, the present study is warranted to identify the active compounds from the dichloromethane and ethanolic leaves extract and examine their PPARγ binding and glucose uptake activity. The ground dried leaves were macerated successively in dichloromethane and ethanol and dried and fractionated using vacuum liquid chromatography. Exhaustive chromatographic procedures yielded to a new tetramethoxyflavonoid, quercetin tetramethyl ether-3-O-ß-L-rhamnoside (1), along with a known quercetin tetramethyl ether (2) and a steroid (3). Compound 2 showed the highest PPARγ binding and glucose uptake activities at 0.313 and 2.5 µg/ml, respectively. The leaves extract and compounds 1–3 showed no cytotoxicity when evaluated using HepG2 cells. Molecular docking result showed that compound 2 is able to interact with important residues within the hydrophobic pocket of the ligand-binding domain, thus acting as an agonist of PPARγ.
Keywords: Connaraceae, cytotoxicity, stigmast-4-one-3-ene, rosiglitazone, diabetes.